Big Five Personalities and Auditors' Ability to Detect Fraud: The Application of Digital Forensics as A Moderation Variable - Dina Dwi Oktafiana; Anis Chariri (Green Publisher Indonesia, 2025)
This study aims to obtain empirical evidence regarding the big five personality traits of each auditor and their ability to detect fraud, assisted by digital forensics. The study involves several auditors from the Central BPK RI. The Theory of Planned Behavior (TPB) is used as the main theoretical foundation of this research because TPB is a behavioral theory that arises from the intention to behave and reflects the individual's traits and the abilities of a profession (auditor) to make decisions based on their work results, which is a form of behavioral attitude. Additionally, digital forensics is applied in this study as a moderating variable, expected to enhance the auditors' ability to detect fraud and weaken the relationship between certain Big Five personality traits of the auditors. This quantitative research uses the Structural Equation Modelling Partial Least Square (SEM-PLS) analysis method. The independent variables in this study are openess to experience, conscientiousness, extraversion, agreeableness, and neuroticism. The dependent variable is the auditors' ability to detect fraud, and the moderating variable is the application of digital forensics. The survey method was conducted by distributing Google Form questionnaires, and 172 respondents were obtained. Data processing was done using SmartPLS 3.2.9 software. The analysis results show that openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism influence auditors' ability to detect fraud, and the application of digital forensics has an impact on strengthening auditors' personalities with high scores on the dimensions of openess to experience, extraversion, conscientiousness and neuroticism.